STK39 blockage by RNA interference inhibits the proliferation and induces the apoptosis of renal cell carcinoma - Zhao, Qi (Onco Targets Ther, 2018)
AIM: Renal cell carcinoma (RCC), the most frequent type of primary renal malignancies, has a high mortality rate. Serine/threonine kinase 39 (STK39) is associated with various human diseases, including cancers. The current study aimed to investigate the functions of STK39 in RCC. MATERIALS AND METHODS: STK39 expression levels in RCC and paired normal renal tissue samples were detected by real-time polymerase chain reaction and Western blotting analyses. The biological functions of STK39 were explored in two RCC cell lines with STK39 silence. RESULTS: STK39 expression was significantly increased in RCC tissues than in normal renal tissues. Suppression of STK39 expression in ACHN and 786-0 cells significantly suppressed cell proliferation and induced cell apoptosis. Consistently, the expression of PCNA and Bcl-2 was remarkably increased, while the expression of Bax was significantly in STK39 knockdown cells compared to control cells. Furthermore, gene set enrichment analysis identified STK39 as an important regulator of p53 and p38 signaling pathways. STK39 knockdown increased p53 expression and inhibited p38 phosphorylation. Moreover, ectopic expression of STK39 in ACHN cells resulted in a reduced p53 expression and increased c-Myc and p-p38 expression. Such effects were suppressed by p38 inhibitor (SB203580). CONCLUSION: STK39 may exert its oncogenic function in RCC through p38 signaling. Our data suggest that STK39 may represent a potential therapeutic target against RCC.